2023
DOI: 10.18196/jai.v24i2.17220
|View full text |Cite
|
Sign up to set email alerts
|

Is information transparency important for funders? A case study of sharia P2P lending companies in Indonesia

Abstract: Research aims: This study explores the importance of information transparency for funders as parties who provide funding to borrowers' projects. It also analyzes information transparency practices in sharia P2P lending.Design/Methodology/Approach: The study used a qualitative case study, focusing on three sharia P2P lending companies in Indonesia. Data were collected through interviews with parties from three sharia P2P lending companies and 11 funders.Research findings: It was found that information transpare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Abdullah Munir's research (2023) found that no Sharia P2P Lending platform in Indonesia has an independent Sharia supervisory board to ensure compliance with Islamic rules, even though this is an obligation according to the DSN MUI fatwa. Likewise, Oktaviani & Dewi (2023) found many gaps in information regarding the status of Sharia compliance on Sharia P2P Lending platform websites, which indicated weak accountability and transparency regarding Sharia aspects due to the absence of adequate supervision and regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Abdullah Munir's research (2023) found that no Sharia P2P Lending platform in Indonesia has an independent Sharia supervisory board to ensure compliance with Islamic rules, even though this is an obligation according to the DSN MUI fatwa. Likewise, Oktaviani & Dewi (2023) found many gaps in information regarding the status of Sharia compliance on Sharia P2P Lending platform websites, which indicated weak accountability and transparency regarding Sharia aspects due to the absence of adequate supervision and regulations.…”
Section: Introductionmentioning
confidence: 99%